Application of a new diagnostic approach to a bovine genital campylobacteriosis outbreak in a Saskatchewan beef herd - Waldner, Cheryl (Canadian Veterinary Medical Association, 2013)
A new real-time quantitative polymerase chain reaction (qPCR) test was used to diagnose Campylobacter fetus subsp. venerealis infection associated with dramatic reproductive losses in a commercial cow-calf herd. The results were verified with repeated culture, phenotypic characterization of the organism and DNA sequencing. This case demonstrates the need for a practical field test for C. fetus subsp. venerealis and the importance of considering this organism as a potential cause of pregnancy failure in beef herds.